2020
DOI: 10.1158/1078-0432.ccr-20-1065
|View full text |Cite
|
Sign up to set email alerts
|

Immune Escape After Adoptive T-cell Therapy for Malignant Gliomas

Abstract: Purpose: Immunotherapy has been demonstrably effective against multiple cancers, yet tumor escape is common. It remains unclear how brain tumors escape immunotherapy and how to overcome this immune escape.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…It appears evident that an understanding of the biology of how the TME shapes the pattern and levels of immune-cell infiltration and exhaustion will be a key factor for the success of ACT. 162 This understanding could provide the biological knowledge to pharmacologically modulate the key pathways of immunoevasion prior to or during the administration of ACT to the patients. Furthermore, drugs could be administered to tumour fragments ex vivo during the manufacturing of the cell product to increase TIL expansion and activation.…”
Section: Ex Vivo Drug Modulation Modifications Of Culturing Conditionmentioning
confidence: 99%
“…It appears evident that an understanding of the biology of how the TME shapes the pattern and levels of immune-cell infiltration and exhaustion will be a key factor for the success of ACT. 162 This understanding could provide the biological knowledge to pharmacologically modulate the key pathways of immunoevasion prior to or during the administration of ACT to the patients. Furthermore, drugs could be administered to tumour fragments ex vivo during the manufacturing of the cell product to increase TIL expansion and activation.…”
Section: Ex Vivo Drug Modulation Modifications Of Culturing Conditionmentioning
confidence: 99%
“…There are three general ways by which cancer cells evade the immune system (Wildes et al, 2020). First, cancer cells alter surface membrane molecules that fool cytotoxic T-cells into perceiving them as unsuitable prey.…”
Section: Anti-predator Adaptations In Cancermentioning
confidence: 99%
“…In glioma, recent studies have reported that immunotherapy such as anti-PD-1 and anti-VEGFA could predominantly prolong the survival of some glioma patients, but the response population was not stable, only a subset of patients could benefit from immunotherapy ( Sandmann et al, 2015 ; Lyon et al, 2017 ; Schalper et al, 2019 ). The immunotherapy limitation may be due to the high heterogeneity of gliomas and their complex immune escape mechanisms ( Jackson et al, 2019 ; Wildes et al, 2020 ). Thus, investigating the molecular heterogeneity and potential immune escape mechanisms of gliomas may contribute to the development of immunotherapy.…”
Section: Introductionmentioning
confidence: 99%